CALCULATION OF UNCERTAINTY VALUE IN THE SKIN THICKNESS TEST USING A THICKNESS MEASUREMENT - Eko Nuraini; Prasetyo Hermawan (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2022)
The manufacture of handicraft products or footwear requires materials according to standards. One of the materials for footwear products is tanned leather, the leather requires a certain thickness according to what has been required, this concerns the comfort and aesthetic value of the product being made. Producers of leather-based crafts need to know the thickness of the leather that will be used as the raw material. The problem is that laboratory personnel in carrying out tests have not carried out or made uncertainty calculations on the test results. The aim of the research is to calculate the uncertainty value of the sample test results with the thickness parameter. The activities will be carried out from May to June 2022 at the ATK Yogyakarta Polytechnic Physical Testing Laboratory. The material used for the box shell for the test method uses SNI 06-7128-2005. The tools used were thicknesses, tables, silver ink and stationery for the test treatment procedure ten times. The results of the study yielded data with an average value of 1.081; standard deviation of 0.02165; standard uncertainty value of calibration (µK) of 0.01; standard uncertainty value of precision (µP) of 0.0125 and a combined uncertainty value of 0.1468. Conclusion the thickness of the box skin is 1.081 ± 0.1468 so that the skin sample meets the requirements of SII 06-0234-1989 on a quality standard of 0.8-1.7 mm thick.